The development of physics learning tools to improve critical thinking skills - Izaak Hendrik Wenno; Anatasija Limba; Yessy Greintje Marged Silahoy (International Journal of Evaluation and Research in Education (IJERE), 2022)
One of the essential physics skills for students in today's era is critical thinking skills. This study offered physics learning tools with a scientific approach to improve critical thinking skills. The purpose of this research was to produce learning documents in the form of lesson plans, teaching materials, and Lorentz force physics test instruments with a scientific approach in improving students' critical thinking skills. This was research and development with a 4D model and steps, including the defining stage, namely the initial stage, to identify the problem. Then, the designing stage was carried out by developing the initial draft of learning tools and research instruments. Afterwards, the developing stage was the initial draft of the improvement stage based on the validation of experts, practitioners, limited trial, and piloted. The data collection instruments in this study consisted of validation sheets, test instruments to measure the implementation of teaching materials, observation sheets to observe teacher and student activities, tests to measure critical thinking skills, and questionnaire responses. The results proved that learning tools developed with a scientific approach improve students' critical thinking skills. Thus, scientific-based physics learning tools is recommended to be used as teaching materials for physics students to improve students' critical thinking skills.